Hipnoterapi Sugesti Langsung dan Anchoring terhadap Penurunan Kecemasan dan Tingkat Depresi pada Pasien ODHA - Sugiyono Sugiyono; Rohman Azzam; Mustikasari Mustikasari; Wati Jumaiyah; Dian Novianti K (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of direct suggestion hypnotherapy and anchoring on reducing levels of anxiety and depression in PLWHA patients at Tarakan Hospital, Central Jakarta. This research method uses Quasi Experiment Design. The results of the Chi-square test showed that after the intervention, the level of anxiety and depression was obtained in the intervention and control groups for the anxiety variables p: 1,000 (> 0.05) and depression p: 0.621 (> 0.05). However, before and after, there was a significant change in the value of anxiety (16.7%), depression (33%) after hypnotherapy. In conclusion, there is no effect of giving direct suggestion hypnotherapy and anchoring techniques on reducing levels of anxiety and depression in PLWHA patients. Keywords: Anchoring, Depression, Direct Suggestion Hypnotherapy, Anxiety, PLWHA